The changes of pharmacokinetic behavior of the medical substances as a consequence of the „in vivo” interaction with general anesthetics - Năstasă V.,; Maria-Magdalena Nechifor (Medicamentul Veterinar)
General anesthetics are substances which produce a reversible state of unconsciousness and insensibility. Inaddition to these principal effects, anesthetics modify almost always, the other functions of the organism. The concentration of the pharmacological agent at its receptor sites and at the target organs will depend on its absorption, distribution, biotransformation and its elimination. Frequently, anesthesia considerably affects these factors, with implications on the pharmacokinetic dynamics of some pharmacological agents. The interaction phenomenon between the general anesthetic substances and other drugs is emphasized.